Pengaruh Shopee Live, Brand Ambassador K-Pop EXO, Dan Brand Image Terhadap Keputusan Pembelian Pada Produk Scralett Whitening Di E-Commerce Shopee Studi Kasus Pada Konsumen Scralett Kota Semarang - Yunita Tri Arviani; Jaya Ramadaey Bangsa (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to determine the influence of Shopee Live, EXO's k-pop Brand Ambassador, and Brand Image on purchasing decisions for Scarlett Whitening products on Shopee e-commerce. The location of this research was conducted on Scarlett Whitening consumers in Semarang City. This type of research uses quantitative research and the methods used are survey research and associative approach research. The main instrument of this research is a questionnaire with 100 respondents using the Slovin formula. Data collection was obtained by distributing questionnaires to Scarlett Whitening consumers in Semarang City who were selected using purposive sampling. Data processing uses Microsoft Excel and IBM SPSS Version 25 software. The data analysis used is multiple linear regression analysis. The research results concluded from the data analysis of the F test results showing that Shopee Live, Brand Ambssador K-Pop EXO, and Brand Image simultaneously had a positive influence on purchasing decisions for Scarlett Whitening products on e-commerce Shopee. Furthermore, data analysis of the T test results shows that Shopee Live does not have a partial positive influence on the decision to purchase Scarlett Whitening on Shopee e-commerce, while the K-Pop EXO Brand Ambassador and Brand Image have a partial positive influence on the decision to purchase Scarlett Whitening on e-commerce. Shopee commerce.